Clinical and Morphological Features of the Course of Thrombocytopathies in Children - Khikmatovna, Abdullaeva Manzura (American Journal of Bioscience and Clinical Integrity, 2025)
Thrombocytopathies in children represent a significant clinical challenge, often leading to bleeding disorders and complications. These conditions, characterized by platelet dysfunction rather than thrombocytopenia, can be inherited or acquired and manifest through abnormal bleeding tendencies. Despite advances in diagnostic techniques, there remains a knowledge gap in understanding the full spectrum of clinical and morphological features of thrombocytopathies in pediatric populations. This study aims to bridge this gap by examining the clinical presentation and morphological alterations associated with thrombocytopathies in children. Using a cohort of pediatric patients diagnosed with thrombocytopathies, we employed a combination of clinical assessments, laboratory tests, and platelet morphology evaluation under light and electron microscopy. Our findings revealed a diverse range of platelet abnormalities, including defective aggregation and impaired response to agonists, along with varying degrees of bleeding manifestations such as easy bruising, prolonged bleeding after minor trauma, and, in some cases, spontaneous hemorrhages. The results suggest that early recognition of thrombocytopathies in children is crucial for appropriate management, which may include platelet function tests and genetic screening. Additionally, the study underscores the need for better diagnostic protocols and more research into tailored therapeutic interventions. These findings have significant implications for clinical practice, highlighting the importance of considering thrombocytopathies in differential diagnoses for pediatric bleeding disorders and guiding future research directions in platelet dysfunction disorders.